Balance of individuals at different age involved in physical activity - review of publications - Angelika Winiarska; Anna Ziółkowska; Konrad Świtaj; Paweł Wojtczak (Kazimierz Wielki University, 2017)
Balance is what we call the ability to control the center of gravity over the support plane in a given environment (also defined as the ability to maintain a vertical position of the body without the help of another person and the ability of regaining  balance during and after motion). Not only is inner ear responsible for mandating balance but also proprioceptors, cerebellum,  properly functioning nervous system and well-trained movement organs or efficient effector.  Postural control also is also affected by genetic conditions and primitive reactive strategies. Included to them are ankle strategy, that is restoring the center of gravity only by movements of the hocks, the hip strategy which is restoring the center of gravity by violent hip movements and step-by-step strategy in which making a step is required to restore the center of gravity. The balance system is quite complex. Damage to even on of the element of this system causes postural instability. In the case of disturbance of balance system , it can be indirectly influenced by nervous system through feedback, priming motion and motor control learning. Improved balance can be achieved with equivalent training. The aim of the study was to analyze different authors' research on athlete balance. Five selected research articles on athletes have been analyzed. The authors have demonstrated a high level of effectiveness in balance training in the process of developing and improving the sense of balance. Individuals who have been in the past or are physically active now retain a better body balance.